2002
DOI: 10.1002/macp.200290038
|View full text |Cite
|
Sign up to set email alerts
|

Copolymers from Methacrylic Acid and Trimethylsilyl Methacrylate ‐ Synthesis, Reactivity Ratios and Thermal Properties

Abstract: Copolymers from methacrylic acid (1) and trimethylsilyl methacrylate (2) have been synthesized by free radical copolymerisation and by controlled desilylation of poly(trimethylsilyl methacrylate) (3). The reactivity ratios were r1 = 2.75, r2 = 0.004. Differential scanning calorimetry showed a linear correlation between the peak temperature of the endotherm for the formation of cyclic anhydrides and the content of methacrylic acid in the copolymer. Obviously, the acid catalyses this reaction. The copolymers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These values are found taking into account the average of the whole reactivity ratios obtained from two experimental and two theoretical methods. In the Q – e scheme, Q reflects the reactivity of a monomer and e represents the polarity of a monomer, which indicates the energy of the localization, order and π‐electron density of a given monomer's polymerizable, ethylenically unsaturated group . A positive value for e indicates that a monomer has a relatively low electron density and is an acceptor monomer, as is the case for AA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are found taking into account the average of the whole reactivity ratios obtained from two experimental and two theoretical methods. In the Q – e scheme, Q reflects the reactivity of a monomer and e represents the polarity of a monomer, which indicates the energy of the localization, order and π‐electron density of a given monomer's polymerizable, ethylenically unsaturated group . A positive value for e indicates that a monomer has a relatively low electron density and is an acceptor monomer, as is the case for AA.…”
Section: Resultsmentioning
confidence: 99%
“…In the Q-e scheme, Q reflects the reactivity of a monomer and e represents the polarity of a monomer, which indicates the energy of the localization, order and π -electron density of a given monomer's polymerizable, ethylenically unsaturated group. 28 A positive value for e indicates that a monomer has a relatively low electron density and is an acceptor monomer, as is the case for AA. A low or negative value for e indicates that a monomer has a relatively high electron density and is a donor monomer, as is the case for VTAz.…”
Section: Reactivity Ratiosmentioning
confidence: 97%
“…Furthermore, methacrylates have been used in biomedical applications for many years and have been shown to promote the adhesion and proliferation of endothelial cells when tethered to adhesive proteins (Fussell and Cooper, ). Polymers containing methacrylic acid and trimethylsilyl methacrylate have also been described to improve adhesion between the resist film and the wafer surface, as well as dry etch resistance in photolithographic applications (Mormann and Ferbitz, ). RGD is a well‐known cell attachment peptide (Bellis, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, RAFT polymerization was selected to synthesize silylated methacrylic polymers with controlled molecular weight distributions, well‐defined chain architectures, and low polydispersity. Some studies of trialkylsilyl methacrylate homopolymerization and copolymerization have been reported16 for applications in photoresists of polymers,17–19 in dry etch resistance of polymers,20 and in antifouling paints 21–23. However, no studies, until now, have been reported on the living radical polymerization of trialkylsilyl methacrylate monomers.…”
Section: Introductionmentioning
confidence: 99%